“Bridging Knowledge to Practice: Effectiveness of a Nurse-Led Community-Based Intervention on Menstrual Hygiene among Adolescent Girls in Rural Haryana” - Purnima Sharma,; Vedamurthy.R,; Reena,; kalpana Mohan, (The Bioscan, 2026)
Background: Menstrual hygiene management is a significant public health concern among adolescent girls, particularly in rural areas where awareness and access to sanitary resources remain limited. Poor menstrual practices contribute to reproductive tract infections, school absenteeism, and reduced quality of life. Nurses play a crucial role in delivering community-based health education to address these gaps. Objectives: The study aimed to assess the effectiveness of a Nurse-led community-based intervention on knowledge and practices regarding menstrual hygiene among adolescent girls.